Application of various mixtures of medicinal herbs in the diet of laying hens: Evaluating preventive approach of fatty liver syndrome - Mohammadreza Khodaei; Mehran Torki; Fariborz Khajali; Iraj Karimi (PLoS ONE, 2025)
Fatty liver hemorrhagic syndrome (FLHS) is a major health issue in laying hens, which is associated with reduced productive performance and increased mortality. This study investigated the efficacy of three herbal additive mixes as dietary interventions to prevent FLHS in a total of 384 LSL-Lohmann laying hens from 65 to 77 weeks of age. Hens were allocated to eight treatments in a 2 × 4 factorial design, comprising two basal diets—a standard diet (SD) and a high-energy, low-protein challenge diet (CD)—alongside four dietary interventions (three herbal mixes and a control). The herbal mixes were formulated as follows: Mix 1 (turmeric, fumitory, green tea, milk thistle), Mix 2 (lemon, black pepper, sumac, chicory), and Mix 3 (garlic, artichoke, ginger, shallot). Productive performance, blood variables, and liver lesion scores were carefully assessed. The results demonstrated that the CD decreased feed intake (FI; P = 0.0001), egg production (EP; P = 0.0001), and egg weight (EW; P = 0.0001) from week 5 onward. Birds received the CD had poorer feed conversion ratio (FCR) as opposed to the SD in weeks 5 and 6 of the trial. Feeding the CD resulted in higher circulatory levels of aspartate aminotransferase (AST; P = 0.0001) and triglycerides (TG; P = 0.0001), and a higher frequency of severe livers scores (P = 0.002). Notably, Mix 2 emerged as the most effective intervention, significantly reversing the negative impacts of the CD across all measured parameters. However, the herbal mixes did not significantly affect heterophil and lymphocyte counts or hemoglobin (Hb) concentration when fed with the CD. Overall, the CD significantly impaired productive performance and increased liver pathological lesions. However, supplementing the CD with Mix 2 (lemon, black pepper, sumac, and chicory) consistently led to the most significant improvements across all measured parameters, proving to be an effective dietary intervention to prevent FLHS in laying hens.